Ultrasonic NaDES-based optimization of luteolin extraction technology from celery (Apium graveolens) for improved drug raw material independence - Putra, Rizky Yulion; Mariska, Ruri Putri; Latifah, Putri Ningrum Nurin (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Natural deep eutectic solvents (NaDES) represent a significant advancement in the field of natural material extraction, offering a novel approach to the isolation of active compounds. The objective of this study was to develop a novel NaDES-based extraction method to achieve the highest percentage of luteolin compounds in celery (Apium graveolens) through ultrasonic treatment. Method: Choline chloride was employed as the hydrogen bonding acceptor (HBA), while lactic acid and malic acid served as the hydrogen bonding donors (HBD). Treatment optimization was conducted using Design Expert 7 software, with the variables comprising the HBA:HBD ratio, temperature, and time. Results: The optimal combination of NaDES solvents was identified as choline chloride: lactic acid and choline chloride: malic acid at a ratio of (4.71 mol: 4.76 mol) and (1.27 mol: 1.71 mol), respectively, at a temperature of 55.2°C. The optimal conditions were 40°C and 35.45°C, with a time of 15.63 minutes and 12.73 minutes, respectively, which yielded 2.2789% and 0.0102% with a desirability of 0.2788 and 0.0408, respectively. Conclusion: The optimal combination was identified as choline chloride: lactic acid, which demonstrated a gain of over 2%. Additionally, the combination of choline chloride: malic acid proved effective for luteolin extraction.